(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
In this paper an attempt will be made to carry out an approach to the ortegan concept of historicity, as it is exposed by the Spanish philosopher in some of his crucial texts. Likewise, it will seek to show how this concept is related and framed in Ortega’s broader theory of human life. In summary, the objective of this paper is one: to develop an approach to the concept of historicity and its relationship and place within the theory about human life in Ortega y Gasset. On the other hand, some possible similarities (and differences) of the ortegan focusing with respect to other related authors, such as Heidegger and Sartre, will be indicated in broad strokes. To achieve the aforementioned, Ortega’s texts will be taken into account: History as a system, Man and people, Ideas and beliefs, Asking for a Goethe from within and For the “Archive of the Word”; on the texts of Heidegger and Sartre, these will be adequately indicated in their time and place.